ANALISIS PENGENDALIAN PERSEDIAAN DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) GUNA MENINGKATKAN EFISIENSI PRODUKSI PADA KEDAI FLOSS CIBITUNG - Ramadani, Teguh; Rohaeni, Heni; Maulia, Indah Rizky (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the control of raw material inventory at Kedai Floss Cibitung using the Economic Order Quantity (EOQ) method to improve production efficiency. Kedai Floss faces challenges in managing raw material stock, which often causes inventory shortages and hampers operations. With the EOQ method, the optimal order quantity is calculated to minimize ordering and storage costs. The results of the study indicate that the application of the EOQ method can reduce total inventory costs by 25% and increase production efficiency by 15% compared to conventional management methods. This study also recommends determining safety stock and reorder points for more optimal inventory management.